Dendrimer: An update on recent developments and future opportunities for the brain tumors diagnosis and treatment - Kaurav, Monika; Ruhi, Sakina; Al-Goshae, Husni Ahmed; Jeppu, Ashok Kumar; Ramachandran, Dhani; Sahu, Ram Kumar; Sarkar, Ashish Kumar; Khan, Jiyauddin; Ashif Ikbal, Abu Md (Frontiers in Pharmacology, 2023)
A brain tumor is an uncontrolled cell proliferation, a mass of tissue composed of cells that grow and divide abnormally and appear to be uncontrollable by the processes that normally control normal cells. Approximately 25,690 primary malignant brain tumors are discovered each year, 70% of which originated from the glial cells. It has been observed that the blood-brain barrier (BBB) limits the distribution of drugs into the tumour environment, which complicates the oncological therapy of malignant brain tumours. Numerous studies have stated that nanocarriers have demonstrated significant therapeutic efficacy for the brain diseases. The present review which is based on a non-systematic search of the existing literature offers an update on the existing knowledge of types of dendrimers, synthesis methods, and mechanisms of action in relation to brain tumors. It also discusses the use of dendrimers in the diagnosis and treatment of brain tumours and the future possibilities of dendrimers. Dendrimers are of particular interest in the diagnosis and treatment of brain tumours because they can transport biochemical agents to the tumour via the BBB and into the brain after systemic administration. Novel therapeutics such as prolonged release of drugs, immunotherapy and antineoplastic effects are developed using dendrimers. The use of PAMAM, PPI, PLL and surface engineered dendrimers has proven revolutionary in the effective diagnosis and treatment of brain tumours.